Summer 2024 in northern Fennoscandia was very likely the warmest in 2000 years - Mika Rantanen; Samuli Helama; Jouni Räisänen; Hilppa Gregow (npj Climate and Atmospheric Science)
Abstract Summer 2024 was exceptionally warm in northern Fennoscandia, with June-August mean temperatures at several long-term weather stations surpassing the long-standing record set in 1937. In this region, summer mean temperatures have been reconstructed from tree-ring proxies, which provide annually resolved and millennium-long records of past climate. Here we show, using in-situ observations and two different tree-ring reconstructions, that summer 2024 was the warmest summer in 2000 years in northern Fennoscandia. Employing an attribution method based on Coupled Model Intercomparison Project Phase 6 climate models, we further estimate that climate change increased the likelihood of this extreme season by a factor of 93 (5–95% uncertainty range 19–881) and increased the temperature an additional 2.1 °C (1.4–2.8 °C). Atmospheric circulation patterns influencing both summers 1937 and 2024 were largely similar, suggesting a comparable large-scale circulation influence. Our findings highlight the impact of climate change for the contemporary heat extremes in Fennoscandia, indicating that the warming of summer climate is emerging from its range of natural climate variability over the last two millennia.